Germanistik studieren in Albanien. Tendenzen und Probleme - Bushati, Endira; Kadzadej, Brikena (2022)
In this article, we will critically examine German studies at universities in Tirana and Shkodra. After a general, but historically well-grounded introduction of the German studies in Albania, we will discuss the basic elements of the structure such as the content of the three-year German studies in Tirana and Shkodra. In this contribution, a special place is given to the current situation of German studies concerning the challenges of the law after the last university reform. Because of our many years of teaching activity and experience in this area, we will try above all to present the problems, tendencies and perspectives of studying German in Tirana and Shkodra in all their contexts. Our considerations represent the attempt to continue or revive the international discussion on this topic.
Keywords: German studies in Albania; problems; tendencies; challenges